STATISTICAL APPROACH FOR DIAGNOSIS OF DISEASES USING HISTOPATHOLOGY DATA - L. MARGREAT,; G. HARI KRISHNAN, (International Journal of Pharma and Bio Sciences, 2015)
The incisional biopsy images of these types of diseases are diagnosed by specialist pathologist by observing the variation in shape, size, colour and density of particular object as the basic parameter. The final conclusion is based on pathological physician observation with his personal knowledge, clinical trials, experience and analytical ability. The conclusion given by a physician may vary with other physician due to the variation in knowledge, experience and analytical ability. The resultant of which may lead to wrong conclusion sometimes. To have a stable diagnosis with the assistance of expertise physician in pathology, an image processing tool has been developed using Matlab. The tool consists of Entropy Calculation, Highest Grey, Kurtosis calculation, Lowest Grey, Variance Calculation and STD calculation.